66.2k views
3 votes
Please help and thank you

Please help and thank you-example-1
User Brigadir
by
4.8k points

2 Answers

4 votes

Answer:

C

Explanation:

Given

m =
(y_(2)-y_(1)  )/(x_(2)-x_(1)  ) ( cross- multiply )

y₂ - y₁ = m(x₂ - x₁) ( subtract y₂ from both sides )

- y₁ = m(x₂ - x₁) - y₂

Multiply through by - 1

y₁ = - m(x₂ - x₁ ) + y₂, thus

y₁ = y₂ - m(x₂ - x₁ ) → C

User Petobens
by
5.2k points
3 votes

Answer:

C

Explanation:


m=(y_2-y_1)/(x_2-x_1) \\ \\ y_2-y_1=m(x_2-x_1) \\ \\ -y_1=-y_2+m(x_2-x_1) \\ \\ y_1=y_2-m(x_2-x_1)

User SeriousLee
by
4.2k points